Software Engineering Approaches for Offshore and Outsourced Development First International Conference, SEAFOOD 2007, Zurich, Switzerland, February 5-6, 2007, Revised Papers - Meyer, Bertrand; Joseph, Mathai (Programming and Software Engineering, 2007)
SEAFOOD for Thought Headline-grabbing though it may be, the software industry's large-scale allo- tion of work to developing countries has not so far generated much technical analysis. Attention is usually limited to the possible political and economic c- sequences, in particular the fears of loss of employment in the West. The aim of the present volume is di?erent. We recognize that o?shore development is here to stay, and not just a result of cost considerations. It is - more accurately - a form of distributed development, relying on advances in communications to let the software industry, in our globalizedworld,bene?t from the wide distribution of human talent. But it is also the source of a new set of challenges, to which accepted software engineering principles and techniques have not completely prepared us. Producing high-quality software on time and within budget is hard enough when the QA team is across the aisle from the core developers, and the customers across the street; what then when the bulk of the development team is across an ocean or two? The ?rst SEAFOOD - Software Engineering Advances For Outsourced and 1 O?shore Development - conference (prompted by an earlier article ) was an - tempt not only to bring software engineering to outsourcing but also to bring outsourcing into the collective consciousness of the software engineering c- munity. This is bene?cial to both sides: successful outsourcing requires strong softwareengineering guidance, but researchin the ?eld must for its part account forthenewworldofsoftwaredevelopment.